2D mixed convection non-Darcy model with radiation effect in a nanofluid over an inclined wavy surface - Bejawada, Shankar Goud; Reddy, Yanala Dharmendar; Jamshed, Wasim; Eid, Mohamed R.; Safdar, Rabia; Nisar, Kottakkaran Sooppy; Mohamed Isa, Siti Suzilliana Putri; Alam, Mohammad Mahtab; Parvin, Shahanaz (Elsevier, 2022)
The two-dimensional radiating mixed convective flowing in a nanofluid, together with the non-Darcy penetrable material over an inclined wavy surface is examined. The conversion from the wavy surface into a smooth surface is performed, via coordinate transformation. The early stage of a mathematical formulation is converted into a group of ordinary differential equations (ODEs), where these ODEs are resolved applying the bvp4c coding via MATLAB. The comparison of the current findings with the previously published studies proved that the current results are quite consistent, and the numerical bvp4c method is acceptable. The influence of relevant factors on nondimensional fluid flowing areas, heat and mass transmission rates is investigated and listed in the table as shown. The wavy surface and tendency angle have an effect of reducing the temperature and concentration in assisting flow. Additionally, the opposite direction is noted for opposing flow occurrences.